Establishment and application of a two‐stage reaction equilibrium model for underground coal gasification. (25th August 2022) - Li, Guangpeng; Duan, Tianhong; Li, Xiang; Wang, Zuotang; Zhang, Peng
Summary: Gasification parameters are basic and original parameters in the design and operation process of gasification projects. In the present research, the conventional reaction equilibrium model was proposed to be a two‐stage reaction equilibrium model to calculate the gasification parameters of underground coal gasification (UCG). The simulated pyrolysis experimental method of UCG was established to obtain the parameters of pyrolysis gas. Afterward, the appropriate heat loss rate (HLR) was determined and gasification parameters were calculated according to the modified reaction equilibrium model. Then, the ultimate gasification parameters were calculated according to the data obtained from the two‐stage reaction equilibrium model. The accuracy of the proposed model was verified by comparing the calculated gasification parameters to the field testing parameters of the Ankou coal mine. The proposed two‐stage modified reaction equilibrium model for UCG can be applied by considering the special characteristics of pyrolysis in UCG and the appropriate HLR value. Abstract : Gasification parameters are basic and original parameters in the design and operation process of gasification projects. In the present research, the conventional reaction equilibrium model was proposed to be a two‐stage reaction equilibrium model to calculate the gasification parameters of underground coal gasification (UCG). The simulated pyrolysis experimental method of UCG was established to obtain the parameters of pyrolysis gas.